PENGARUH BRAND PERSONALITY DAN BRAND AWARENESS TERHADAP LOYALITAS PENGGUNA IPHONE DI BENGKULU - Imelda Rahma Siregar; Meiffa Herfianti; Merta Kusuma (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze how Brand personality and Brand awareness affect the loyalty of iphone users among UMB management students. The research method used is quantitative with a multiple linear regression approach. Data was collected through a questionnaire that was distributed to respondents who were iphone users. The sample used was 120 respondents. The results of the study showed that there was a positive and significant influence of brand personality on user loyalty, with a t-value of 4.583 and a significance of 0.000. This shows that Brand Personality is in the good category. In addition, brand awareness also has a positive effect on user loyalty, with a t-value of 8.413 and a significance of 0.000 which shows that it is in the good category. Furthermore, the results of the simultaneous analysis (f-test) showed that Brand Personality (X1) and Brand Awareness (X2) together or simultaneously had a significant influence on User Loyalty, with a calculated f value of 130,288 and a significance of 0.000. This proves that these two variables complement each other in providing a better experience to users. Keywords: Brand Personality and Brand Awareness, and Loyalty User